2018
DOI: 10.3748/wjg.v24.i43.4950
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and potential pathogenesis of colorectal cancer-related ischemic stroke

Abstract: AIMTo investigate the specific biomarkers and potential pathogenesis of colorectal cancer-related ischemic stroke (CRCIS).METHODSA retrospective study was conducted on CRCIS patients (colorectal cancer patients with ischemic stroke without conventional stroke risk factors) registered at seven centers between January 2007 and December 2017. Clinical data and laboratory and imaging findings were compared with age- and sex- matched patients with colorectal cancer (CRC) without ischemic stroke that were admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
(48 reference statements)
1
13
0
Order By: Relevance
“…Similar results were found in our previous studies. 7,9 Increased levels of serum CA125, a type of mucin that is secreted by the cancer cell, were found to be related to hypercoagulability ischemic stroke in patients with cancer. 25 Moreover, autopsy experiments confirmed that there were mucin components that were secreted by cancer cells in the blood vessels, and they were thromboembolic in patients with cancer and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in our previous studies. 7,9 Increased levels of serum CA125, a type of mucin that is secreted by the cancer cell, were found to be related to hypercoagulability ischemic stroke in patients with cancer. 25 Moreover, autopsy experiments confirmed that there were mucin components that were secreted by cancer cells in the blood vessels, and they were thromboembolic in patients with cancer and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that the occurrence of CRIS was related to independent risk factors that were derived from serum, and the independent risk factors for CRIS are heterogeneous because they have different pathological types. [7][8][9] It was suggested that the characteristics of specific pathological types of CRIS risk factors may identify CRIS and may even predict its occurrence. Bladder cancer is the tenth most frequent cancer worldwide and the most common urinary tract malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…This was a retrospective study of patients with ECIS from January 2011 to December 2020 at The First Affiliated Hospital of Guangxi Medical University, The Second Affiliated Hospital of Guangxi Medical University, The Ninth Affiliated Hospital of Guangxi Medical University, Fusui County People's Hospital, Wuzhou Red Cross Hospital, Cenxi People's Hospital and The Wuming Hospital of Guangxi Medical University. Based on a previous definition of cancer-related ischemic stroke, [12][13][14] we defined ECIS as acute ischemic stroke in patients with active EC and without conventional stroke risk factors. In the present study, we defined the conventional stroke risk factors as the presence of hypertension, diabetes, hyperlipidemia, atrial fibrillation, valvular heart disease, and cerebral artery stenosis.…”
Section: Patient Selectionmentioning
confidence: 99%
“…11 Moreover, our previous studies have found that every confirmed cancer-related ischemic stroke has its own unique clinical characteristics and risk factors, suggesting that targeting a certain type of cancer-related ischemic stroke will be more conducive to discovering the clinical characteristics and pathogenesis of cancer-related ischemic stroke. [12][13][14] For example, colorectal cancer-related ischemic stroke was associated with elevated CEA and neutrophils, 12 kidney cancerrelated stroke was associated with elevated plasma D-dimer, CA125 and CEA levels, and increased urine protein levels, 13 and breast cancer-related ischemic stroke was associated with endocrine therapy, elevated plasma D-dimer and CA153 levels. 14 Esophageal cancer (EC) is one of the most common digestive tract tumors worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in various countries have found that the incidence of AIS is significantly higher in cancer patients than in noncancer patients [1][2][3][4][5][6][7], but the specific causes are not clear. Most of the authors suggested in published articles that the biological indicators we should focus on cancer-associated AIS patients were D-dimers and carbohydrate tumor markers [8][9][10][11][12]. However, the research concerning clinical characteristics, risk factors, pathogenesis, and survival situation of cancerassociated AIS patients were rare.…”
Section: Introductionmentioning
confidence: 99%